Anti-proliferative effect and induction of apoptosis in androgen-independent human prostate cancer cells by 1,5-bis(2-hydroxyphenyl)-1,4-pentadiene-3-one - Citalingam, Kamini; Abas, Faridah; Lajis, Nordin H.; Othman, Iekhsan; Naidu, Rakesh (MDPI, 2015)
Curcumin has poor in vivo absorption and bioavailability, highlighting a need for new curcumin analogues with better characteristics in these aspects. The aim of this study is to determine the anti-cancer properties of four selected curcumin analogues, on the cytotoxicity, proliferative and apoptotic effects on androgen-independent human prostate cancer cells (PC-3 and DU 145). Initial cytotoxicity screening showed MS17 has the highest cell inhibitory effect, with EC50 values of 4.4 ± 0.3 and 4.1 ± 0.8 µM, followed by MS13 (7.5 ± 0.1 and 7.4 ± 2.6 µM), MS49 (14.5 ± 1.2 and 12.3 ± 2.3 µM) and MS40E (28.0 ± 7.8 and 30.3 ± 1.9 µM) for PC-3 and DU 145 cells, respectively. Time-dependent analysis also revealed that MS13 and MS17 displayed a greater anti-proliferative effect than the other compounds. MS17 was chosen based on the high selectivity index value for further analysis on the morphological and biochemical hallmarks of apoptosis. Fluorescence microscopy analysis revealed apoptotic changes in both treated prostate cancer cells. Relative caspase-3 activity increased significantly at 48 h in PC-3 and 12 h in DU 145 cells. Highest enrichment of free nucleosomes was noted at 48 h after treatment with MS17. In conclusion, MS17 demonstrated anti-proliferative effect and induces apoptosis in a time and dose-dependent manner suggesting its potential for development as an anti-cancer agent for androgen-independent prostate cancer.